Strategi Efektif Bimbingan Karier Di Smk Muhammadiyah Imogiri Untuk Mengarahkan Alumni Ke Peminatan Kerja Yang Sesuai Dengan Keterampilan Dan Minat Siswa - Wiranthi Prastomo; Tri Kuat; Samekto Wibowo; Erwan Ariyanta; Sabarudin Ahmad (Journal on Education, 2024)
In the era of globalization and rapid industrial development, Vocational High School (SMK) graduates face challenges in finding a career path that matches their skills and interests. This study aims to explore effective career guidance strategies at SMK Muhammadiyah Imogiri that can lead alumni to relevant job specializations. The study analyzed the guidance strategies implemented, the role of guidance counseling teachers, and industry involvement in the career guidance program. The results showed that structured and relevant career guidance strategies, the active role of counseling teachers, as well as industry involvement through internship programs and workshops, are very influential in preparing students towards careers that match their potential. Constraints in the implementation of career guidance were also identified, as well as recommended strategies to overcome them. Implementation of the recommended strategies includes the integration of skills and interest assessments and the development of a comprehensive career guidance curriculum. This research is expected to assist SMKs in improving the effectiveness of career guidance, so that alumni are better prepared to enter the workforce and achieve professional success.